Boosting Cultural Tourism: The Significance of the 'Great Steppe Nomads World' Festival and Boraldai Saka Mounds (Journal of Philosophy, Culture and Political Science, 2024)
Abstract: Tourism, a fast-growing global sector, significantly boosts socioeconomic development and regional growth. Cultural tourism, which involves the consumption of tangible and intangible heritage, attracts millions of visitors annually through traditions, monuments, music, dance, and the arts. The festival sector, promoting cultural interaction at various levels, is one of the fastest-growing areas in tourism, supporting local economies and industry growth. Since 2016, Kazakhstan has hosted the biennial "Great Steppe Nomads World" International Ethno-Cultural Festival. This festival, featuring nomadic sports, traditional music, dance, and crafts, aims to celebrate and preserve Central Asian nomadic heritage. Despite its significance, local awareness of the festival and the Boraldai Saka mounds archaeological complex is limited. This research aims to increase local awareness of the "Great Steppe Nomads World" Festival and the Boraldai Saka mounds. Objectives include conducting a descriptive analysis of the festival, surveying Almaty residents' awareness, creating a documentary film to enhance recognition, and assessing the film's impact on interest in visiting the festival and archaeological complex. This study underscores the importance of cultural tourism in promoting local heritage and fostering international exchange.Keywords: cultural tourism, the "Great Steppe Nomads World" International Ethno-Cultural Festival, the Boraldai Saka mounds archaeological complex, documentary film